Antecedentes da intenção de rotatividade: comprometimento organizacional e confiança do empregado na organização - Carmo, Giselle do (2009)
Investigating turnover intention in the work place has been the topic of many studies and professionals. This is due to the fact that the organizational context has changed dramatically over the past decades and a professional s understanding of what to expect from the organization has also changed. The present study aims at testing a model which considered the Organizational Commitment (affective, calculative and normative) and the Trust of the employee to the organization as an antecedent to Turnover Intention. The sample comprises of 139 employees from different companies and segments who answered consistent and validated scales: Organizational Commitment (affective, calculative and normative), Trust of the employee to the organization and Turnover Intention. Not only were the scales developed, but also a questionnaire about personal and professional data. Descriptive analyses and multiple regressions have been, then, carried through, considering the measure of Turnover Intention as a dependent variable. In order to test the model, it was conducted a Stepwise multiple regression analysis. The proposed model was partially confirmed. The results indicates that the affective organizational commitment explain 50% of the variance of Turnover Intention. The variable Losses of Investment explain 6%, and the variable Norms relative to the Resignation explain 2% of the variance of Turnover Intention .These results were analyzed and compared with others empirics studies, and the conclusions corroborate findings in the Organization Behaviors. Further researches were proposed.